MENINGKATKAN PRESTASI BELAJAR SISWA MATA PELAJARAN IPA DENGAN METODE DISCOVERY DI KELAS VII-5 SMP NEGERI 1 PATUMBAK - Dina Haloho (JS (JURNAL SEKOLAH), 2019)
Abstract: Improving Student Learning Achievement in Science Subjects with Discovery Method in Class VII-5 Middle School 1 Patumbak. Cycle I the average value of student learning achievement is 70.00 and mastery learning reaches 67.57% or there are 25 students out of 35 students who have finished learning. Cycle II the average value of student achievement is 77.03 and mastery learning reaches 78.38% or there are 29 students out of 35 students who have finished learning Cycle III the average value of formative tests is 83.24 and of 35 students who have completed 33 students and 2 students have not reached mastery learning. Through the results of this study indicate that discovery learning has a positive impact in improving student achievement. This can be seen from the increased learning completeness of the first, second and third cycles, namely 67.57%, 78.38%, and 89.19%, respectively.Keywords: Learning achievement, Discovery Method, Natural Science LearningAbstrak: Meningkatkan Prestasi Belajar Siswa Pada Mata  Pelajaran IPA Dengan Metode Discovery Di Kelas VII-5 SMP Negeri 1 Patumbak. Siklus I nilai rata-rata prestasi belajar siswa adalah 70,00 dan ketuntasan belajar mencapai 67,57% atau  ada 25 siswa dari 35 siswa sudah tuntas belajar. Siklus II nilai rata-rata prestasi belajar siswa adalah 77,03 dan ketuntasan belajar mencapai 78,38%  atau ada 29 siswa dari 35 siswa sudah tuntas belajar Siklus III nilai rata-rata tes formatif sebesar 83,24 dan dari 35 siswa yang telah tuntas sebanyak 33 siswa dan 2 siswa belum mencapai ketuntasan belajar. Melalui hasil peneilitian ini menunjukkan bahwa pembelajaran penemuan (discovery) memiliki dampak positif dalam meningkatkan prestasi belajar siswa. Hal ini dapat dilihat dari ketuntasan belaja rmeningkat dari sklus I, II, dan III yaitu masing-masing 67,57%, 78,38%, dan 89,19%.Kata kunci: Prestasi  belajar, Metode Discovery, Pembelajaran IPA